Waist-to-Height Ratio – Reference Values and Associations with Cardiovascular Risk Factors in a Russian Adult Population - Kholmatova K; Krettek A; Dvoryashina IV; Malyutina S; Cook S; Avdeeva E; Kudryavtsev AV (Diabetes, Metabolic Syndrome and Obesity, 2025)
Kamila Kholmatova,1– 3 Alexandra Krettek,1,4,5 Irina V Dvoryashina,3 Sofia Malyutina,6,7 Sarah Cook,8 Ekaterina Avdeeva,6 Alexander V Kudryavtsev2 1Department of Community Medicine, UiT The Arctic University of Norway, Tromsø, Norway; 2International Research Competence Centre, Northern State Medical University, Arkhangelsk, Russia; 3Department of Hospital Therapy and Endocrinology, Northern State Medical University, Arkhangelsk, Russia; 4Department of Public Health, School of Health Sciences, University of Skövde, Skövde, Sweden; 5Department of Internal Medicine and Clinical Nutrition, Institute of Medicine, Sahlgrenska Academy at University of Gothenburg, Gothenburg, Sweden; 6Scientific Research Institute of Internal and Preventive Medicine, Branch of Federal Research Centre Institute of Cytology and Genetics, Siberian Branch of the Russian Academy of Sciences, Novosibirsk, Russia; 7Department of Therapy, Hematology and Transfusiology, Novosibirsk State Medical University, Novosibirsk, Russia; 8School of Public Health, Faculty of Medicine, Imperial College London, London, UKCorrespondence: Kamila Kholmatova, Department of Community Medicine, UiT The Arctic University of Norway, PO Box 6050, Langnes, NO-9037, Tromsø, Norway, Email kkholmatova@mail.ruPurpose: Waist-to-height ratio (WHtR) is an anthropometric index with limited data on its population distribution. The aim was to establish WHtR reference values and investigate WHtR associations with socio-demographic, lifestyle and clinical characteristics in Russian adults.Methods: We used data from the population-based cross-sectional Know Your Heart study (2015– 2018, Arkhangelsk and Novosibirsk, N = 4495, 58.1% of women, 35– 69 years, mean age 54.0). Age-adjusted WHtR reference values for the total study population and by sex were modeled as marginal 5th-95th percentiles (P5-P95) through quantile regressions. WHtR associations with cardiovascular biomarkers were assessed using linear regressions.Results: The conventional WHtR threshold of 0.5 for abdominal obesity was the value of P25, while P50 and P75 values were 0.54 and 0.60. In ages 35– 49 years, P5-P50 values were higher in men. In the age group 60– 69 years, P25-P95 values were higher in women. In both sexes, WHtR was associated with age, city of residence, not having university education and low physical activity; in women – with poor financial situation, in men – with being married, non-smoking and hazardous drinking. Among clinical parameters, C-reactive protein had the strongest positive association with WHtR in both sexes, while HDL cholesterol had the strongest negative association. Each standard deviation (SD) change in ln-transformed C-reactive protein was associated with 0.435 and 0.321 SD increase in WHtR in women and men, respectively. One SD increase in HDL cholesterol was associated with − 0.334 SD change in WHtR in women and with corresponding change of − 0.297 SD in men. In women, WHtR had stronger associations with age, university education, poor financial situation, blood pressure, HDL cholesterol, and ln-transformed C-reactive protein, in men – with being married, current smoking, LDL and non-HDL cholesterol, and HbA1c.Conclusion: Three-quarters of the study population had WHtR values exceeding the conventional threshold for abdominal obesity. Men and women differed in the WHtR associations with socio-demographic and lifestyle risk factors, biomarkers of inflammation, hypertension, dyslipidemia, and diabetes. WHtR is a useful cardiovascular risk indicator in a Russian adult population.Keywords: waist-to-height ratio, reference values, obesity, Russia